Leukemic pleural effusion in AML-M0: Unusual presentation - Tandon, Anchal; Acharya, Seema; Bhardwaj, Aparna; Kala, Pooja (Indian Journal of Case Reports, 2019)
Extramedullary disease in AML-M0 is a rare occurrence. It is even rarer to encounter breathlessness as primary presenting complaint secondary to a leukemic pleural effusion. Leukemic pleural effusion occurs rarely in acute myeloid leukemia (AML) with minimal differentiation. Patients with AML usually present with weakness, hemorrhage, and recurrent infections. The highest incidence of extramedullary leukemic manifestation is seen in monocytic AML. Here, we report the case of an 18-year-old male who presented withbreathlessness and vocal cord palsy. Examination and investigation established diagnosis of an acute myeloid leukemia M0 with leukemic pleural effusion.